Duplicación de retenciones de la fuente del impuesto a la renta, en la empresa Dipor S.A. en la ciudad de Babahoyo en el año 2022. - Camposano Gonzales, Andrés Gustavo (2022)
This case study is carried out in the company Dipor S.A, a private company belonging to the Arca Continental Group and The Coca-Cola Company, is located in the city of Babahoyo, in the streets KM 3.5 Via Jujan-Babahoyo, is carried out to investigate the cause and effect of fictitious values in favor of customers by doubling withholdings of the source of income tax.